PENERAPAN PEMBELAJARAN INKUIRI HIPOTETIS UNTUK MENINGKATKAN AKTIVITAS DAN MEMAHAMKAN SISWA MATERI BARISAN DAN DERET - Endang Trinoviawati; Subanji Subanji; I Made Sulandra (FMIPA UNIVERSITAS NEGERI MALANG, 2019)
Sequence and series have been taught directly through theory from books, making it difficult for students to link between concepts or between theories, so that there are still many students who can only solve problems limited to what has been exemplified by the teacher. This study aims to describe the application of hypothetical inquiry learning that can increase student activity and understand the sequence and series material. This research is a classroom action research conducted in April 2017. The research subjects were 38 students of class X IPA 5 SMAN 8 Malang. The results showed that applying hypothetical inquiry in learning could increase student activity and learning completeness. The increase in student activity from 11% in cycle I to 63% active criteria in cycle II, the percentage of students completing in cycle I, namely 63%, increased to 92% in cycle II.